06.04 Synergistic antitumor activity of pan-PI3K inhibition and immune checkpoint blockade in bladder cancer. (21st September 2022) - Pan, C; Zhu, Z; Zhu, S; Ma, A; Chittepu, VCSR; Farrukh, H; Cheng, F
Abstract : Background: Immune checkpoint blockade (ICB) induces durable response in approximately 20% of advanced bladder urothelial cancer (aUC) patients. Over 50% of aUCs harbor genomic alterations along the phosphoinositide 3-kinase (PI3K) pathway. The goal of this project was to determine the synergistic effects and mechanisms of action of PI3K inhibition and ICB combination in aUC. Materials and Methods: Alterations affecting the PI3K pathway were examined in The Cancer Genome Atlas (TCGA) and the Cancer Dependency Map databases. Human and mouse cells with PTEN deletion were used for in vitro studies. C57BL/6 mice carrying syngeneic tumors were used to determine in vivo activity, mechanisms of action and secondary resistance of pan-PI3K inhibition, ICB and combination. Results: Alterations along the PI3K pathway occurred in 57% of aUCs in TCGA. CRISPR knockout of PIK3CA induced pronounced inhibition of cell proliferation ( p = 0.0046). PI3K inhibition suppressed cancer cell growth, migration and colony formation in vitro . Pan-PI3K inhibition, anti-programmed death 1 (PD1) therapy and combination improved the overall survival (OS) of syngeneic mice with PTEN-deleted tumors from 27 days of the control to 48, 37 and 65 days, respectively. In mice with tumors not containing a PI3K pathway alteration, OS was prolonged by the combination, but not single treatments. Pan-PI3K inhibition significantly upregulated CD80, CD86, MHC-I and MHC-II in dendritic cells, and downregulated the transforming growth factor beta pathway with a false discovery rate (FDR)-adjusted q-value of 0.001. Interferon alpha response was significantly upregulated with anti-PD1 therapy (q value: < 0.001) and combination (q value: 0.027). Compared to the control, combination treatment increased CD8 + T cell infiltration ( p = 0.005), decreased Treg cell infiltration ( p = 0.036), and upregulated the expression of multiple immunostimulatory cytokines and Granzyme B ( p < 0.01). Secondary resistance was associated with upregulation of the mammalian target of rapamycin (mTOR) pathway and multiple Sprr family genes. Conclusions: The combination Pan-PI3K inhibition and ICB has significant anti-tumor effects in aUC with or without activated PI3K pathway and warrant further clinical investigation. This combination creates an immunostimulatory tumor milieu. Secondary resistance is associated with upregulation of the mTOR pathway and Sprr family genes. Base on this study, a Phase II clinical trial has been designed. Disclosure Information: C. Pan: None. Z. Zhu: None. S. Zhu: None. A. Ma: None. V.C.S.R. Chittepu: None. H. Farrukh: None. F. Cheng: None.